Cloud Computing with iPlant Atmosphere. Issue 1 (16th February 2018) - McKay, Sheldon J.; Skidmore, Edwin J.; LaRose, Christopher J.; Mercer, Andre W.; Noutsos, Christos
Abstract: Cloud Computing refers to distributed computing platforms that use virtualization software to provide easy access to physical computing infrastructure and data storage, typically administered through a Web interface. Cloud‐based computing provides access to powerful servers, with specific software and virtual hardware configurations, while eliminating the initial capital cost of expensive computers and reducing the ongoing operating costs of system administration, maintenance contracts, power consumption, and cooling. This eliminates a significant barrier to entry into bioinformatics and high‐performance computing for many researchers. This is especially true of free or modestly priced cloud computing services. The iPlant Collaborative offers a free cloud computing service, Atmosphere, which allows users to easily create and use instances on virtual servers preconfigured for their analytical needs. Atmosphere is a self‐service, on‐demand platform for scientific computing. This unit demonstrates how to set up, access and use cloud computing in Atmosphere. Curr. Protoc. Bioinform . 43:9.15.1‐9.15.20. © 2013 by John Wiley & Sons, Inc.